The Implementation Method in Senior High School Physical Sports and Health Education Teacher to The Assessment of Learning Outcomes (Revision of Curriculum 2013) in Pemalang District - Susilo, Azis Hendro; Soegiyanto, Soegiyanto; Awang, Fajar (Journal of Physical Education and Sports, 2019)
This study to determine the implementation methods in Senior High School physical sports and health education teacher to the assessment of learning outcomes (revision of Curriculum 2013) in Pemalang District. The research method used is descriptive with survey, observation and documentation methods. The subjects of this study were Senior High School in Pemalang District, consisting of 19 schools, both public and private. The results of the study show that (1) the implementation of the assessment of Curriculum 2013 related to learning devices states that it is appropriate with a percentage of 84%, (2) the implementation of the assessment of Curriculum 2013 related to attitude assessment, knowledge assessment, and assessment of skills in the appropriate category with a percentage of 79.1%, (3) the difficulties of the physical sports and health education teacher related to the assessment of Curriculum 2013 are (a) making the lesson plan (RPP) too complicated (b) the dishonest students when making evaluations between friends, (c) the results of the oral and written tests not harmonizing so the results are out of sync.